2020
DOI: 10.1186/s12944-020-01408-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of statins and LDL-cholesterol target attainment in Turkish patients with type 2 diabetes - a nationwide cross-sectional study (TEMD dyslipidemia study)

Abstract: Background Attaining acceptable levels of LDL Cholesterol (LDL-C) significantly improves cardiovascular (CV) outcomes in patients with type 2 diabetes mellitus (T2DM). The LDL-C target attainment and the characteristics of patients attaining these targets were investigated in this study. Furthermore, the reasons for not choosing statins and the physicians’ attitudes on the treatment of diabetic dyslipidemia were also examined. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…In recently published TEMD dyslipidaemia study, which was conducted in nationwide tertiary endocrine units in Turkey between 01 April and 30 June 2017 also demonstrated a 20.5% LDL‐C target attainment (32.7% in high‐risk and 10.8% in very high‐risk groups) in patients with DM 24 . In TEMD study, of the type II diabetics only 24.5% had had cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…In recently published TEMD dyslipidaemia study, which was conducted in nationwide tertiary endocrine units in Turkey between 01 April and 30 June 2017 also demonstrated a 20.5% LDL‐C target attainment (32.7% in high‐risk and 10.8% in very high‐risk groups) in patients with DM 24 . In TEMD study, of the type II diabetics only 24.5% had had cardiovascular disease.…”
Section: Discussionmentioning
confidence: 94%
“…The LDL-C (<100 mg/dL) and BP (<130/80 mmHg) goal achievement rates were 25% and 23% in the ADMIRE study (27), while 35% and 20% in the IDMPS study, respectively (28). In the TEMD Dyslipidemia Study among 4,504 T2D patients, only 8.4% of patients attained target LDL-C levels, and 44.8% of patients were on statin treatment despite the need for statin therapy in 89.5% along with achieving target LDL-C levels by only a quarter of patients on statin therapy (30). Data from TEMD Hypertension Study in 4,756 T2D patients revealed hypertension in 67.5% of patients and 87.4% of hypertensive patients received treatment; BP was on target only in 52.7% of patients (31).…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that maintaining blood pressure values below 140/85 mmHg is associated with a statistically significant reduction in the incidence of DKD in patients with hypertension and T2DM over a 4-year follow-up [ 103 ]. However, real-world evidence suggests that, despite the improvements in risk-factor control and diabetes management, glycemic, blood pressure, and LDL-cholesterol target levels are achieved only in a small proportion of T2DM patients, especially if concomitantly affected by CKD [ 101 , 104 , 105 , 106 ]. These gaps in diabetes care might be generally explained by several factors, such as the patients’ lack of motivation, the therapeutic inertia by the care providers, and, more generally, the logistical or financial barriers in the patients’ access to care [ 101 ].…”
Section: Critical Issues On Dkd Management: Evidence From Real-world Settingsmentioning
confidence: 99%